Trace Elements and Minerals in Fumarolic Sulfur: The Case of Ebeko Volcano, Kuriles. (20th March 2018) - Shevko, E. P.; Bortnikova, S. B.; Abrosimova, N. A.; Kamenetsky, V. S.; Bortnikova, S. P.; Panin, G. L.; Zelenski, M.
Abstract : Native sulfur deposits on fumarolic fields at Ebeko volcano (Northern Kuriles, Russia) are enriched in chalcophile elements (As-Sb-Se-Te-Hg-Cu) and contain rare heavy metal sulfides (Ag2 S, HgS, and CuS), native metal alloys (Au2 Pd), and some other low-solubility minerals (CaWO4, BaSO4 ). Sulfur incrustations are impregnated with numerous particles of fresh and altered andesite groundmass and phenocrysts (pyroxene, magnetite) as well as secondary minerals, such as opal, alunite, and abundant octahedral pyrite crystals. The comparison of elemental abundances in sulfur and unaltered rocks (andesite) demonstrated that rock-forming elements (Ca, K, Fe, Mn, and Ti) and other lithophile and chalcophile elements are mainly transported by fumarolic gas as aerosol particles, whereas semimetals (As, Sb, Se, and Te), halogens (Br and I), and Hg are likely transported as volatile species, even at temperatures slightly above 100°C. The presence of rare sulfides (Ag2 S, CuS, and HgS) together with abundant FeS2 in low-temperature fumarolic environments can be explained by the hydrochloric leaching of rock particles followed by the precipitation of low-solubility sulfides induced by the reaction of acid solutions with H2 S at ambient temperatures. The elemental composition of native sulfur can be used to qualitatively estimate elemental abundances in low-temperature fumarolic gases.